New morphological and anatomical data on the genus Fuernrohria (Apiaceae) - Bani̇, Bariş; Mavi̇ İdman, Dudu Özlem (Phytotaxa, 2020)
In this study, morphological and anatomical data (including fruit micromorphological characters) of the genus Fuernrohria were studied and compared with the related genera Grammosciadium, Caropodium and Vinogradovia. The morphological description of Fuernrohria setifolia, which is the only known species in the genus, is expanded. Photos of inflorescences, infructescences and leaves of the species taken from the wild are provided. Leaf segment and mericarps are illustrated, and also the distribution area of the genus is mapped. Anatomical features of root, stem, leaf sheath, leaf segment and fruit are presented with photographs of cross sections for each of them. Vegetative anatomical characteristics of the species and micromorphological description of fruit are given and exhibited for the first time in the present study. The results show that two important diagnostic characters for Fuernrohria are determined for the first time as “shape and size of commissural vittae in mericarps” and “number of vascular bundles in leaf cross section”.